2018
DOI: 10.1161/circulationaha.118.035202
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Cardiomyocyte NLRP3 Inflammasome Signaling Promotes Atrial Fibrillation

Abstract: -Atrial fibrillation (AF) is frequently associated with enhanced inflammatory response. The "NACHT, LRR and PYD domain containing protein 3" (NLRP3)-inflammasome mediates caspase-1 activation and interleukin-1β release in immune cells, but is not known to play a role in cardiomyocytes (CMs). Here, we assessed the role of CM NLRP3-inflammasome in AF. -NLRP3-inflammasome activation was assessed by immunoblot in atrial whole-tissue lysates and CMs from patients with paroxysmal (pAF) or long-standing persistent (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
324
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 438 publications
(386 citation statements)
references
References 76 publications
16
324
2
2
Order By: Relevance
“…In addition, as already described (Fig. 3), histological analysis did not reveal increased LA fibrosis in the sham group, as would be expected in rats exposed to systemic inflammation 31,32 .…”
Section: Characterization Of Intrinsic Af Substrate In the Implantedsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, as already described (Fig. 3), histological analysis did not reveal increased LA fibrosis in the sham group, as would be expected in rats exposed to systemic inflammation 31,32 .…”
Section: Characterization Of Intrinsic Af Substrate In the Implantedsupporting
confidence: 85%
“…This intriguing finding led us to several additional experiments in order to try to reveal possible source\s for this phenomenon. The results strongly argue against the involvement of systemic inflammation as an underlying mechanism based on direct serum measurements of inflammatory cytokines as well as the absence of atrial fibrosis which is expected to occur in the presence of systemic inflammation 31,32,46 . Post-operative AF due to the thoracotomy we performed in the implantation surgery is another option that should be considered.…”
Section: Scientific Reports |mentioning
confidence: 84%
“…Besides that, emerging evidence indicated enhanced inflammatory responses in patients with AF and accompanied by increased circulating levels of pro‐inflammatory cytokines . Further, NLRP3 inflammasome activation was recently shown to be involved in the pathogenesis of AF . Because AF is able to exacerbate inflammation and atrial fibrosis that further perpetuates the arrhythmia, reduction of inflammation and reversal of structural remodelling have increasingly become the focus of new therapeutic strategies for the prevention of AF …”
Section: Introductionmentioning
confidence: 99%
“…NOD-like receptor protein 3 (NOD-like receptor protein 3, NLRP3) inflammasome, as a participant of the inflammatory immune response, is closely related to cardiovascular diseases [20]. Numerous studies have confirmed that NLRP3 inflammasome is involved in the occurrence and development of myocardial I/R injury, cardiomyopathy, arrhythmia, and other diseases [21][22][23]. However, there are no reports on the role of NLRP3 inflammasome activation in myocardial I/R injury and metformin-related intervention studies.…”
Section: Introductionmentioning
confidence: 99%